Implementation of the Concept of Islamic Montessori Education at Awliya Holistic Elementary School, Majasem Cirebon - Rahayu, Sari (Eduprof : Islamic Education Journal, 2025)
One of the main challenges of Islamic education in Indonesia is to find a learning model that is able to balance intellectual growth with spiritual and moral development. The Montessori method, known for its focus on independence, sensory learning and Developmental Psychology, provides significant opportunities to develop autonomy and creativity. However, without a spiritual foundation, this approach risks neglecting the upbringing of children's religious and ethical values. The purpose of this study is to explore how Montessori approach can be integrated with Islamic values in the context of Primary School holistic Awliya (SDH) Majasem Cirebon. Particular attention is paid to the application of fitrah (innate human disposition), adab (ethics and manners), and tazkiyat al-nafs (purification of the soul) in the practice of daily learning. This study uses descriptive qualitative methods using classroom observation, curriculum analysis, and in-depth interviews with teachers, parents, and students. The Data were analyzed thematically to identify patterns of integration between Montessori principles and Islamic values. These findings suggest that Montessori practices-such as prepared environments, freedom with responsibility, and experiential learning-are effectively aligned with the values of Islamic education. This integration fosters not only intellectual independence but also spiritual awareness, ethical discipline, and emotional balance in students. In conclusion, The Montessori-Islamic model implemented in the Awliya Holistic Primary School is a pioneering effort in the reform of Islamic education in Indonesia. It offers a contextual and holistic framework capable of producing intellectually capable, spiritually grounded, and morally responsible students.